2018
DOI: 10.1371/journal.pone.0197370
|View full text |Cite
|
Sign up to set email alerts
|

Immunity levels to poliovirus in Lao children and adults before the vaccine-derived poliovirus outbreak: A retrospective study

Abstract: In 2015, several provinces in Lao People's Democratic Republic (Lao PDR) experienced a vaccine-derived poliovirus outbreak. This survey was conducted (i) to evaluate the vaccination coverage in different settings and cohorts using the seroprevalence of anti-poliovirus (PV) antibodies as a surrogate measure, and (ii) to explore the usefulness of an ELISA in a country with limited resources and a specific epidemiological setting. IgG antibodies were assessed by ELISA in Lao children (n = 1216) and adults (n = 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…against polio, measles and rubella. Despite the comprehensive vaccination programme, outbreaks of vaccine-preventable diseases (VPD) continue to occur, such as polio (Pauly et al, 2018), measles (Sengkeopraseuth et al, 2018), diphtheria (Nanthavong et al, 2015) and pertussis (Kleine et al, 2020). Outbreaks near to the borders with neighboring countries such as Vietnam have also raised fear of cross-border spread of disease.…”
mentioning
confidence: 99%
“…against polio, measles and rubella. Despite the comprehensive vaccination programme, outbreaks of vaccine-preventable diseases (VPD) continue to occur, such as polio (Pauly et al, 2018), measles (Sengkeopraseuth et al, 2018), diphtheria (Nanthavong et al, 2015) and pertussis (Kleine et al, 2020). Outbreaks near to the borders with neighboring countries such as Vietnam have also raised fear of cross-border spread of disease.…”
mentioning
confidence: 99%
“…Nonetheless, the improved ELISA must be serotype distinct, and negativity thresholds should be studied for the specificity and sensitivity. It should be noted that out of the five examined cohorts, both healthcare workers (cohort 5) and children (cohort 1) were analyzed by VNT 35 . The WOA-RVFL method handled the healthcare workers as a practical example of an adult with a high risk during the outbreak since they are at a higher risk for exposure to infections with a possibility to transfer the infection from a specific cohort to another.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to track the immunization and vaccination in professionals and to ensure their ability to perform critical caring for patients. The WOA-RVFL algorithm can observe the ELISA serologies of the other children and adult cohorts matched with results of groups that tested by VNT 35 . The WOA-RVFL suggests a high efficiency of outreach vaccination activities since the children from the remote area were equally well protected as the fully vaccinated children.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, outbreaks of vaccine-preventable diseases have been reported. 2 , 3 , 4 , 5 Hepatitis B is endemic in Laos and the prevalence of the hepatitis B surface antigen (HBsAg; used as a marker for chronic infection) in the general population is estimated to be 5–6%, based on a recent study published in 2022. 6 Although several studies reported on HBsAg prevalence rates in blood donors, women and children in the past years, it is difficult to understand hepatitis B epidemiology in Laos due to large differences in study populations, study designs and study sites.…”
Section: Introductionmentioning
confidence: 99%